PENGARUH KONFLIK KERJA-KELUARGA DAN KEPUASAN KERJA TERHADAP TINGKAT TURNOVER INTENTION KARYAWAN PADA RESTORAN PIZZA HUT MALL BALI GALERIA - Nanda, Ni Luh Neva Krestya; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2015)
This study was conducted to determine the effect of work-family conflict and job satisfaction on turnover intention. This study is done at Pizza Hut Mall Bali Galeria. Samples taken as many as 60 people with saturated sample method, in which the saturated sample here using the entire population there as a sample. Data was collected through questionnaires using a 5-point Likert scale. The analysis technique used is the path analysis. The results of this study indicate that each variable lonflik work-family and job satisfaction effect on turnover intention in Restaurant Pizza Hut Mall Bali Galeria and indirect effect of work-family conflict on turnover intention through job satisfaction. It shows that work-family conflict negatively affect job satisfaction, and a positive effect on turnover intention. Job satisfaction can reduce the level of turnover intention of employees in the restaurant Pizza Hut Mall Bali Galeria
Keywords: konflik kerja-keluarga; kepuasan kerja; turnover intention